Creative Love in Education - Pinhas Luzon (Theology and Philosophy of Education)
This article examines the integration of theology and critical thought to develop educational love capable of generating transmissible values. Drawing on Rabbi Nachman of Breslov’s philosophy, it argues that expanding apophatic theology through critical thinking can form a transformative educational framework. This love emerges from recognizing human consciousness limitations, fostering a reciprocal teacher-student dynamic. The analysis reveals that acknowledging boundaries paradoxically creates a relationship where mutual recognition transcends preliminary ideologies. Creative Love in Education offers practical applications for classroom environments that honor both individual potential and communal values.